« Écrans de lumière » : l’art du vitrail dans l’architecture de Frank Lloyd Wright - Claude MASSU (E-REA)
This article will survey the use of glass as a modern industrial material in Wright’s architecture and more particularly the art of the stained glass which characterizes Wright among the modernist architects of the early 20th century. While the subject has not been much researched until recently, Wright’s art of the stained glass is an original and essential part of his architectural ideal. Several sources for Wright’s art of the stained-glass windows are considered: the influence of the main representative of the Chicago School of architecture Louis H. Sullivan and his defense of planar decoration, the lessons of Japanese prints and traditional architecture, and the interpretation of organic and natural forms. Forms and functions of stained-glass windows are examined thanks to several examples of Prairie Houses and Californian houses. This study also includes considerations about other types of lighting in Wright’s architecture concerning religious and office buildings. As a conclusion the author emphasizes in Wright’s architecture the decisive role of ornament of which leaded glass is an integral part.